(untitled) (TAMADDUN NURI JURNALI, 2025)
The article studies the formation and development of the young entrepreneurial movement in Surkhandarya region during the years of independence based on a historical and analytical approach. The study analyzes the socio-economic factors, state policy, legal framework and financial support mechanisms that influenced the development of young entrepreneurship. The article examines the successes achieved by young entrepreneurs, the problems they encountered and promising directions for their elimination.